Non-functioning paraganglioma of the bladder: case report and literature review - Silva, Ulysses Messias da (2004)
Introduction: Paragangliomas are pheochromocytomas with an extra-adrenal location. They can be found between the base of the skull and the bladder. They account for less than 0.06% of all bladder tumors, and were first reported by Zimmermann in 1953, and Rodriguez-Rubio in 1975. Case report: A 17 year old male patient was admitted to Alto Vale Regional Hospital with hematuria and urinary retention. He was examined but nothing positive was found, after which he was discharged for outpatient treatment. After the vesical tumor was diagnosed, the patient was admitted to Hospital for elective surgical treatment of the tumor. After this, pathological analysis revealed a paraganglioma, confirmed by immunohistochemistry. Eleven months after surgery, the patient remains healthy and assymptomatic. Discussion: Paragangliomas usually appear between 11 and 70 years, and are clinically classified as functioning or non-functioning depending on cathecolaminergic production by the tumor. Ten to fifteen percent of bladder paragangliomas are malignant. The diagnosis is confirmed by urinary vanilmandelic acid and urinary metanephryns, ultrassonography, excretory urography, cistoscopy, computerized tomography, magnetic nuclear resonance, and 131-metaiodobenzilguanidine iodine cintilography, with the last one being the most sensitive according to the literature. The treatment is surgical, and the prognosis is uncertain due to small number of cases reported.